Syntheses of Silver Nanoparticles Using Two Energies, 300 and 500 mJ of Nd: YAG Laser - Noor Al-Jubbori; Mushtaq Al-Jubbori; Ayyad Alhade Ezwam (مجلة التربية والعلم)
The aim of this paper a prepare silver nanoparticles using the pulsed laser ablation method in liquid (PLAL). This method is considered unconventional, fast, clean, long-lasting, and non-toxic, using a Q-switched pulsed laser (1064 Nd: YAG) nanometers. With two ablation energies (300, 500 mJ)  and a number of pulses (50, 100, 150, 200), the laser ablation process was carried out at room temperature, by immersing the metal in deionized water (distilled water) with (5 mL). After preparing the solutions, we noticed the change in the color of deionized distilled water increases with the number of pulses, this is a good indicator of the production of silver nanoparticles. The color of the solution ranges from pale yellow to dark yellow. The physical properties were analyzed by transmission electron microscope (TEM) at a pulse of 200 and were shown by this examination showed that there were nanoparticles in the prepared solutions of silver, and the results of the TEM images showed that at two energies (300, 500 mJ) spherical silver nanoparticles were obtained, from these images the diameters of  nanoparticles were measured using the (ImageJ) program, it was shown that the diameter distribution range between (4.41 - 42.87 nm), which was approximately centered at (18.13) nm for silver, and at 500mJ laser power the diameter distribution range between (3.12- 26.60 nm), which was approximately centered at (16.67) nm for silver.